The Hölderlinian tragedy and its plastic correlate: the pictorial ouvre of C. D. Friedrich - Martínez Ciriero, Mikel (Escritura e Imagen, 2021)
This article delves into Friedrich Hölderlin’s theoretical writings on tragedy and the tragic, interpreting them in the light of his unfinished tragic work The Death of Empedocles. Subsequently, Hölderlin’s reflection is related to the work of the painter Caspar David Friedrich, described as “tragedy of the landscape”. The comparative study of literature and painting, accompanied by both artists’ own reflections, offers the opportunity to approach from a multiple perspective certain characteristics of the subjectivities represented by the poet and the painter, whose existence appears to be linked to a deep sense of tragedy. Word, image and romantic reflection emerge in this dialogue between the poet and the painter to offer a fertile key to reading the tragic in both its artistic and experiential dimensions.